A rapid synthesis of TiO2 nanotubes in an ethylene glycol system by anodization as a Pt-based catalyst support for methanol electrooxidation. Issue 45 (20th May 2015) - Sui, Xu-Lei; Wang, Zhen-Bo; Xia, Yun-Fei; Yang, Min; Zhao, Lei; Gu, Da-Ming
<x xml:space="preserve">Abstract</x> Titania nanotubes were rapidly fabricated and used as a Pt-based catalyst support. The as-prepared catalyst exhibits a much higher electrochemical activity and durability than the commercial Pt/C.